COMPARISON OF SEXUAL DYSFUNCTION BETWEEN END-TO-END ANASTOMOSIS AND BUCCAL MUCOSA GRAFT - Yuri, Prahara; Wahyudi, Irfan; Rodjani, Arry (Indonesian Urological Association, 2014)
Objective: The aim of this study was to compare long term follow-up of sexual dysfunction between end-to-end anastomosis or buccal mucosa graft in short segment bulbar urethral stricture. Material & Method: We performed a meta analysis of cohort study. The data sources was MEDLINE from 1980 through 2011. A fixed effects model with Mantel-Haenszel method was used to calculate the pooled Risk Ratio (RRs) and 95% Confidence Interval (CIs). We assessed the heterogeneity by calculating the I2 statistic. All analyses were performed with Stata statistical software, version 10.0 (Stata Corp). Results: We analyzed 6 cohort studies. End-to-end anastomosis and buccal mucosa graft patients who complained about sexual dysfunction were 24.6% (45/183) and 9.1% (11/122) respectively, with overall RR 2.54 (95% CI, 0.22-0.69, p = 0.001). Conclusion: Buccal mucosa graft showed a superior outcome compared to end-to-end anastomosis, based on sexual dysfunction in ≤ 3 cm bulbar urethral stricture treatments.Keywords: Sexual dysfunction, end-to-end anastomosis, buccal mucosa graft, anterior urethral stricture.